1999
DOI: 10.1002/1531-8249(199907)46:1<22::aid-ana6>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal activity in the basal ganglia in patients with generalized dystonia and hemiballismus

Abstract: Microelectrode recording was performed in the basal ganglia of 3 patients with generalized dystonia and 1 patient with hemiballismus secondary to a brainstem hemorrhage. Neuronal activity was recorded from the internal and external segments of the globus pallidus and assessed for mean discharge rate and pattern of spontaneous activity. The responses of neurons in the internal segment of the globus pallidus to passive and active movements were also evaluated. Mean discharge rates of neurons in both segments of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

46
330
8
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 490 publications
(387 citation statements)
references
References 47 publications
46
330
8
2
Order By: Relevance
“…During movement, most of these neurons were activated, whereas the activation-to-inactivation ratio was reversed for nonparkinsonian monkeys. 99 In dystonia, experimental recordings showed enlarged receptive fields of dystonic joints in the somatosensory cortex, 100 thalamus, 101 and globus pallidus 102,103 (but also see the 2003 article by Hutchison et al 104 ).…”
Section: Effects On Coactivation Of Competing Motor Programsmentioning
confidence: 98%
“…During movement, most of these neurons were activated, whereas the activation-to-inactivation ratio was reversed for nonparkinsonian monkeys. 99 In dystonia, experimental recordings showed enlarged receptive fields of dystonic joints in the somatosensory cortex, 100 thalamus, 101 and globus pallidus 102,103 (but also see the 2003 article by Hutchison et al 104 ).…”
Section: Effects On Coactivation Of Competing Motor Programsmentioning
confidence: 98%
“…Based on pharmacologic studies, there seems to be a relative increase in the activity of striatal neurons of the direct pathway over those that give rise to the indirect pathway in dystonia [195,196], and single-cell recording studies in patients undergoing functional neurosurgical treatments have demonstrated low discharge rates in both GPe and GPi [197][198][199][200][201][202], in distinction to the aforementioned changes in PD where GPi discharge rates are generally increased. The presence of lowfrequency discharge in the GPi in patients with dystonia is similar to that in other hyperkinetic disorders, including chorea/ ballismus and motor tics [197,203,204]. Other studies have shown the emergence of low-frequency oscillations in single-cell and LFP activities in the basal ganglia or thalamus [200,201,[205][206][207], comparable with those found in PD.…”
Section: Dystoniamentioning
confidence: 99%
“…41 There is an increase in the presence of bursts, low frequency oscillations, and synchronization in neurons in the basal ganglia and thalamus in movement disorders. 22,[42][43][44][45][46][47][48] Such changes in discharge patterns and synchronization play an important role in the pathophysiology of movement disorders. Motor symptoms including tremor, bradykinesia, and rigidity are associated with increased neuronal synchronization and low-frequency rhythmic oscillation, 49 -51 and bursts and oscillations parallel the appearance of motor symptoms in PD.…”
Section: Basal Ganglia and Thalamic Pathophysiology In Movement Disormentioning
confidence: 99%